Effect of Work Environment on Employee Performance at PT. Perkebunan Nusantara XIV (Persero) Makassar - Mujahid; Nasyirah Nurdin; Syamsul Riyadi; Erwin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
This study aims to determine the influence of the work environment on the performance of employees. This study uses a quantitative approach. With the method of data collection the distribution of questionnaires, with 30 respondents who are employees of PT. Perkebunan Nusantara XIV (Persero) Makassar. The technique of data analysis was carried out using simple linear regression, which was used to determine the effect of the independent variable and the dependent variable, namely the influence of the working environment on employee performance. Based on the results of the partial regression coefficient (t-test) research, it shows that the value of tcount is 4.780 > 1.699 with a significance level of 0.000 < 0.05, which means that the hypothesis H0 is rejected and H1 is accepted. It can be concluded that there is a significant effect between work environment variables (X) on employee performance (Y).